ISLAMIC EDUCATION MANAGEMENT STRATEGY IN INTERNALIZING LOCAL CULTURAL VALUES NDOU-NDOU MANSUANA AND HOMALI'A FOR THE FORMATION OF MORALS - Afifuddin; La Ode Muhamad Risal; Nuryamin (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study stems from recognising the importance of character education rooted in local culture as a moral safeguard for the younger generation amid globalisation. In Pada Raya Makmur Village, Wakatobi, the traditions of Ndou-Ndou Mansuana (religious counsel) and Homali’a (customary prohibitions) serve not merely as oral heritage, but as active media for internalising moral and religious values in children’s daily lives. This research deeply explores the internalisation process of these Islam-infused traditions in shaping children’s moral character. Employing a qualitative ethnographic design, data were collected through participant observation, in-depth interviews, and document analysis involving children, parents, customary leaders, and religious figures. Thematic analysis revealed three main themes: the forms and practices of local culture; the moral and religious values (honesty, responsibility, respect, social solidarity, and religious devotion); and a staged internalisation process through introduction, understanding, acceptance, and habituation. Findings show that integrating Ndou-Ndou Mansuana and Homali’a forms a dual-value education model: constructive counsel fostering moral awareness, and preventive prohibitions reinforcing self-control. This study expands the local wisdom-based character education theory and offers practical contributions to education policy, cultural preservation, and community-based parenting strategies. Integrating culture and religion proves effective in preserving tradition while fostering resilient and adaptive moral character in facing contemporary challenges.